Pengaruh Strategi Promosi, Kualitas Produk Terhadap Keputusan Pembelian Bakpia Pathok 25 - Pramudita Maharani, Steffanie; Putra Prasetya, Bangun (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to investigate how Bakpia Pathok 15 purchasing decisions are impacted by promotion approach and product quality. The quantitative approach is utilized. Questionnaires were used to gather data. We utilize the spss tool, version 25, to test our hypotheses and models. This study's findings indicate: Purchase Decisions are Influenced by Promotion. Buying Choices are Influenced by Product Quality. Marketing and Product Satisfaction Affect Consumer Spending.